Penerapan Metode Pembelajaran Snowball Throwing Pada Materi Aljabar Untuk Meningkatkan Hasil Belajar Siswa - Suhartini, Suhartini; Sutarto, Sutarto; Yuliyanti, Sri (Media Pendidikan Matematika, 2017)
Based on information obtained through preliminary observation in MTs. Al-Muslimun NW Tegal, obtained the problem that the participation of students at the time of learning is low. Students do not want to express opinions or ask questions although there is still material that has not been understood. This results in low student learning outcomes. The purpose of this study is to describe the application of Snowball Throwing learning method on algebra material to improve student learning outcomes. The research method used in this research is classroom action research (PTK). Subjects in this study were students of grade VIII MTs. Al-Muslimun NW. The instruments of this study consist of material handouts, teacher and student activity observation sheets, evaluation and documentation tests. Data collection techniques in this study include: data sources, data types, data collection methods. The data analysis technique of individual learning result using KKM determined by school that is â‰¥ 65 and classical completeness using KK determined that is â‰¥ 85%, while teacher activity and student activity is calculated using formula exist in research of class action. The results showed the percentage of classical completeness 93.94% with an average value of 75.61. By looking at the percentage of individual and classical student learning outcomes has been achieved. So it can be concluded that the application of Snowball Throwing learning method can improve student learning outcomes class VIII MTs. Al-Muslimun Tegal.